DISUNITY IN DIVERSITY. - Birnir, Jóhanna Kristín; Van Cott, Donna Lee (Latin American Research Review, 2007)
This paper demonstrates that in Latin America a significant portion of the increased legislative party system fragmentation since the 1980s is explained by the recent political incorporation of ethnic populations. Until now, scholars have likely not identified this relationship because they have not used the nuanced measures of ethnic fractionalization that account for internal diversity of indigenous populations and race, and because they have not focused on the time period when ethnic peoples were politically incorporated. In addition to demonstrating this relationship statistically, we use two case studies from Bolivia and Ecuador to illustrate how in recent years the dynamic relationship between ethnic groups and political parties in Latin American legislatures has changed and resulted in the statistical association between ethnic fractionalization and party system fragmentation that we observe.